ANALISIS KESULITAN BELAJAR MATEMATIKA DISKRIT MAHASISWA TEKNIK INFORMATIKA - Kusumaningrum, Dwi Sulistya; Puspita Lestari, Santi Arum (PRISMA, 2019)
ABSTRACTAsosiasi Perguruan Tinggi Informatika dan Komputer (APTIKOM) states that learning outcomes of Informatics on mathematical topics are discrete mathematics. This study aims to examine the results of students learning discrete mathematics, and examine what factors are causing students difficulty learning discrete mathematics. The method used is a mix method which is qualitative methods and quantitative methods. Data collection as the result of discrete mathematics learning outcomes, and mathematical learning difficulty questionnaire data. The population used is students of Informatics at Buana Perjuangan University Karawang with a sample of 65 students taking discrete mathematics courses in the 2018/2019 school year. The results showed that most students still had difficulty learning discrete mathematics. This is because an average value is 66,4 from the value of a test value is 55. This Test Value is the minimum passing grade. While the factors that cause discrete mathematics learning difficulties are divided into 2 classifications namely 6 influential indicators and 2 quite influential indicators.Â Keyword: Learning Difficulties, Learning Outcomes, Discrete Mathematics